Paediatric Electrophysiologic Studies: How and What With? - N.Sreeram; M.Emmel; U.Trieschmann; E.de Haan (Indian Pacing and Electrophysiology Journal, 2008)
Catheter ablation of arrhythmias in children has become standard practice virtually worldwide. Successful and safe ablation has been made possible by a combination of factors. These include increased operator experience, a better understanding of the natural history of a wide variety of arrhythmias, advances in technology such as smaller catheters, the routine use of various three-dimensional mapping systems, and the development of alternative energy sources. It is also not uncommon to perform multiple catheter intervention procedures (ablation ± intravascular stent implantation ± device closure of residual shunts ± elective pacemaker or device implantation) during a single session. It is important to bear in mind that arrhythmia recurrence is commoner in children in general, and that this is particularly the case with postoperative (scar-related arrhythmias). Despite acute success, long-term follow-up is mandated for this subgroup of patients.